The Inhibitory Activity of Plants from Central Argentina on p-Hydroxyphenylpyruvate Dioxygenase. Isolation and Mechanism of Inhibition of a Flavanone from Flourensia oolepis - Chiari, María Eugenia; Tosoni, Leonardo; Joray, Mariana Belén; Diaz Napal, Georgina Natalia; Palacios, Sara María; Ruiz, Gustavo Miguel; Vera, Domingo Mariano A.; Carpinella, María Cecilia (Planta Medica, 2015)
The enzyme 4-hydroxyphenylpyruvate dioxygenase catalyzes the second step in the tyrosine degradation pathway. In mammals, this enzyme is the molecular target of drugs used for the treatment of metabolic disorders associated with defects in the tyrosine catabolism, mainly the fatal hereditary disease tyrosinemia type 1. This study evaluated the inhibitory effect of 91 extracts on 4-hydroxyphenylpyruvate dioxygenase from mostly native plants from central Argentina. Flourensia oolepis ethanol extract showed itself to be the most effective, and bioguided fractionation yielded pinocembrin (1) as its active principle. This flavanone, with an IC50 value of 73.1 µM and a KI of 13.7 µM, behaved as a reversible inhibitor of the enzyme and as a noncompetitive inhibitor. Molecular modeling studies confirmed the inhibitory potency of 1 and explained its activity by means of in silico determination of its binding mode in comparison to inhibitors of known activity, cocrystallized with 4-hydroxyphenylpyruvate dioxygenase. The main structural determinants that confer its potency are discussed. Analysis of the binding mode of the flavanone 1 with 4-hydroxyphenylpyruvate dioxygenase revealed the basis of the noncompetitive reversible mechanism of inhibition at the molecular level, which seems to be a common feature in this ubiquitous family of natural compounds. The resulting information may establish the basis for obtaining novel 4-hydroxyphenylpyruvate dioxygenase inhibitors for the treatment of tyrosinemia type 1 and other disorders associated with tyrosinase catabolism.
Keywords: Flourensia oolepis; Asteraceae; HPPD inhibitors; Argentinian native plants; pinocembrin; molecular docking